FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PADA BPR NUSAMBA GROUP PERIODE 2013-2015 - Puji Lestari, 14.05.62.0013; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2017)
The purpose of this study is to analyze the influence of Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Assets (ROA), and Non Performing Loan (NPL) to distribution of credit. This research used the rural bank. The population of this study was all rural banks of Nusamba Group network during period 2013 to 2015. The number of samples in this study are 19 rural banks using purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis using SPSS 20. The results of this study showed that the variables of Third Party Funds (TPF) and Loan to Deposit Ratio (LDR) have positive and significant influence to distribution of credit. Meanwhile Capital Adequacy Ratio (CAR) and Return on Assets (ROA) have positive and insignificant influence to distribution of credit, and Non Performing Loan (NPL) has negative and insignificant influence to distribution of credit. Keywords: Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Assets (ROA), Non Performing Loan (NPL), Distribution of Credit